Model of a critical size defect in the New Zealand white rabbit’s tibia - Mohamed Amin, Mohamed Azril; Che Seman, Che Nor Zarida; Awang, Mohd Shukrimi; Zakaria@Mohamad, Zamzuri; Mohd Yusof, Nazri; Buyong, Zunariah; Mohd Khir, Zafirah (2015)
The critical size defect (CSD) has been defined as the smallest intraosseous wound in an animal that will not heal spontaneously within an expected time frame. In the preclinical field of orthopaedics and trauma surgery, CSD has been used as an experimental model for evaluating the effectiveness of newly developed biomaterials. In vivo investigation is important to evaluate the biocompatibility of biomaterial before clinical application. Therefore, the aim of this study is to demonstrate the technical protocol of CSD in rabbit’s tibia for in vivo investigation of new synthetic bone materials.